CREATION AND DEVELOPMENT OF EFFECTIVE MANAGEMENT MECHANISM OF SPORTS FACILITIES - Izzatullayev Sunnatulla Shermuxammad o'g'li (American Journals Publishing, 2023)
Sports facilities are the material and technical basis of sports, including mass sports and physical culture, healthy lifestyle. It is difficult to hope for high results in sports without building and improving sports facilities. "Sport facilities" is a component of sports pedagogy. In this way, pupils and students acquire important knowledge and practical skills such as youth sports facilities, their types, requirements for them.
Keywords: sports complexes, stadium, swimming pool, gym, shooting range, gymnastics, athletics, basketball, volleyball, table tennis.